210 Regulation of TIM-3 by phosphatidylserine. (9th November 2020) - Smith, Courtney; Li, Alice; Krishnamurthy, Nithya; Lemmon, Mark
Abstract : Background: Immune checkpoint blockade has proven effective in targeting exhausted T-cells to reactivate the immune system against cancer. However, the majority of patients fail to respond to currently available therapies, which primarily target PD-1. Thus, a key challenge for checkpoint blockade therapy is to identify and understand new therapeutic targets. Another immune checkpoint receptor is TIM-3, which – like PD-1 – is expressed on exhausted T-cells in the tumor microenvironment. 1, 2 TIM-3 belongs to a family of phosphatidylserine (PS) receptors, including TIM-1 and TIM-4, which have well-documented roles in the engulfment of apoptotic cells by phagocytes. 3 However, the role of PS in regulating TIM-3 function is less clear. We therefore investigated how TIM-3 modulates T-cell signaling and how PS influences TIM-3 activity, with the ultimate goal of improving the translation of candidate TIM-3 therapies to the clinic. Methods: Surface plasmon resonance (SPR) was used to quantify the interaction between human TIM-3 and PS. A Jurkat T-cell model was used to investigate the role of TIM-3 in T-cell receptor (TCR) signaling and to determine the role of PS in regulating TIM-3 function. Results: TIM-3 bound PS-containing membranes with low micromolar affinity in vitro. In the Jurkat cell model system, high – but not low – surface levels of TIM-3 promoted T-cell signaling, suggesting a threshold of receptor expression needed to modulate T-cell signaling, similar to what has recently been reported for PD-1. 4 However, chimeric receptors that maintained the TIM-3 cytoplasmic tail but were unable to bind PS failed to enhance T-cell signaling like the full-length TIM-3 receptor. Cells expressing mutant TIM-3, which displayed reduced PS binding as quantified by SPR, also displayed reduced T-cell signaling compared to cells expressing wild-type TIM-3. Importantly, treatment of TIM-3-expressing cells with a functional TIM-3 antibody that blocks PS binding also reduced T-cell signaling compared with untreated TIM-3-expressing cells. Conclusions: Our results support a role for PS as a ligand capable of modulating TIM-3 activity. Using chimeric receptors, TIM-3 mutants, changes in receptor expression, and a functional TIM-3 antibody, we show that preventing the interaction between TIM-3 and PS blocks TIM-3 activity. These data suggest that blocking the PS-TIM-3 interaction is a key mechanism for functional antibodies targeting TIM-3. Ultimately, this work supports the development and use of clinical antibodies that block the interaction of TIM-3 with PS and provides new mechanistic insight into how TIM-3 modulates TCR signaling. Acknowledgements: This work was supported by the PhRMA Foundation Pre-Doctoral Fellowship in Pharmacology/Toxicology. References: Fourcade J, Sun Z, Benallaoua M, et al. Upregulation of Tim-3 and PD-1 expression is associated with tumor antigen-specific CD8+ T cell dysfunction in melanoma patients. J Exp Med . 2010;207(10):2175–2186. Zhou Q, Munger ME, Veenstra RG, et al. Coexpression of Tim-3 and PD-1 identifies a CD8+ T-cell exhaustion phenotype in mice with disseminated acute myelogenous leukemia. Blood . 2011;117(17):4501–4510. Kobayashi N, Karisola P, Peña-Cruz V, et al. TIM-1 and TIM-4 glycoproteins bind phosphatidylserine and mediate uptake of apoptotic cells. Immunity . 2007;27(6):927–940. Hui E, Cheung J, Zhu J, et al. T cell costimulatory receptor CD28 is a primary target for PD-1-mediated inhibition. Science . 2017;355(6332):1428–1433.